Assessment of fodder yield from Artocarpus lakoocha and Bauhinia purpurea) tree planting in community forests in the western midhills of Nepal - Baral, S.K.; Shakya, R. (Banko Janakari, 2007)
This experiment assessed the yield and growth performance of the fodder tree planting in the community forest focusing on Artocarpus lakoocha, Bahunia purpurea. Major variables analyzing the yield and growth of the species such as dbh, height, green weight of the foliage was measured. After analyzing the data, Artocarpus lakoocha was found to be good yielding and growth performing species as compared to Bahunia purpurea. Preliminary result shows that yield of the both the species is significantly correlated with dbh and height. Key words: Artocarpus lakoocha, Bahunia purpurea, fodder, plantation, community forest, yield Banko Janakari Vol.15(2) 2005 pp3-5